(untitled) (Contemporary Education and Teaching Research, 2023)
In the new era, society has put forward higher requirements for the training of talents in colleges and universities, which needs to keep pace with the development of the times in the Java programming course for college computer majors, and constantly improve and optimize the teaching strategy. From the current situation, there are some problems in the teaching of Java programming courses for computer science majors in colleges and universities, such as the teaching content is not updated in time, the teaching method is too single, etc., which needs to be addressed in the teaching reform to solve the current problems. The article explores the importance of teaching reform of Java programming courses for computer majors in colleges and universities and gives effective teaching strategies according to the current teaching situation.